Effects of Rosiglitazone on Metabolic Parameters and Adiponectin Levels in Fructose-Fed Rats - Atanasovska, Emilija; Jakjovski, Krume; Kostova, Elena; Petlichkovski, Aleksandar; Dimitrovski, Chedo; Bitoska, Iskra; Kikerkov, Igor; Petrovski, Ognen; Labachevski, Nikola (Scientific Foundation Spiroski (publications), 2009)
Aim. To investigate the effect of the peroxisome proliferators-activator receptor gamma agonist, rosiglitazone, on metabolic parameters and adiponectin levels in an animal model of the metabolic syndrome. Material and methods. Metabolic syndrome was induced in 32 male Wistar rats by adding a fructose in drinking water for 12 weeks. During the last 4 weeks, 16 rats were treated with rosiglitazone (5 mg/kg/day), while the remaining 16 did not receive any medication (fructose group). Another control group consumed standard rat chow and water for 12 weeks. Results. Chronic fructose administration induced a significant increase in systolic blood pressure (SBP), body weight, serum triglycerides (TG), free fatty acids (FFA), insulin, glucose AUC0-120 (during oral glucose tolerance test) and decreased serum high density lipoprotein (HDL) cholesterol and adiponectin concentrations compared with the control group. Treatment with rosiglitazone over the final 4 weeks reversed these effects and significantly reduced SBP, TG, FFA, insulin concentrations and glucose AUC0-120 compared with the fructose group. In addition, rosiglitazone increased serum levels of adiponectin twofold from 3.44 ± 0.46 to 7.03 ± 1.30 μg/ ml. Conclusion. This study indicates that rosiglitazone treatment improves the components of the metabolic syndrome, which is accompanied with an increase in adiponectin concentrations.
Keywords: Rosiglitazone; adiponectin; metabolic syndrome; fructose; insulin